“Running from Behind.” An Analysis of the Neighborhood Councils of Montevideo - Paula Ferla; Alejandra Marzuca; Uwe Serdüit; Yanina Welp (Íconos)
With the intention of exploring one of the central themes in current studies on participatory democracy, this study analyzes the influence of institutional design on citizens’ participation, focusing on a concrete experience – the neighborhood councils of Montevideo. With this intention, the following is analyzed: a) the institutional design of these councils, b) the influence of these councils on the definition of public policies, c) their functioning as “citizenship schools,” and d) the levels of citizen support that they convoke. The conclusions of the study signal that design considerably limits the performance of neighborhood councils in terms of both the influence that they have in decision-making and the development of civic virtues and political capital. Thus, it is concluded that declines in participation over time is related to the institution design.